Using Jumbled Sentence Games to Improve the Writing Ability of The Seventh Grade Students of MTs Muhammadiyah 6 Bayat, Klaten - Elsha Pramunindya Wardhani (PBI 15 UMY 042, 2015)
*42 Writing is one of the English skills. Students of MTs Muhammadiyah 6 Bayat admitted that writing English was a difficult skill to master. It also happened at seventh grade students of MTs Muhammadiyah 6 Bayat. The objective of this research was to find out the effectiveness of jumbled sentence games to improve the writing ability of the seventh grade students of MTs Muhammadiyah 6 Bayat. This research also described the level of the seventh grade students’ writing ability of MTs Muhammadiyah 6 Bayat. This research was an action research. The setting and the subject of this research was the seventh grade students of MTs Muhammadiyah 6 Bayat Klaten. The numbers of the students were 24 students. This research was implemented in four cycles. Each cycle had two meetings. The data were gained from pre test and post test. The pre test was given before the treatment and the post test was given in the end of the treatment in each cycle. The topic was based on the KTSP curriculum. The research findings indicated that the jumbled sentence games could improve the students’ writing ability. It was proved by average score of the writing test which increased from the pre test 64.17 to the post test 88.12.The result of analyzing the data is taccount (2.260) is bigger than ttable (1.709). Therefore, Alternative hypothesis (Ha) was accepted the use of jumbled sentences games to improve writing ability of the seventh grade students of MTs Muhammadiyah 6 Bayat. It means the researcher’s hypothesis is accepted. The effectiveness of jumbled sentence games to improve the writing ability of the seventh grade viii students of MTs Muhammadiyah 6 Bayat is medium effect because it was higher than 3 while the threshold for a medium effect. That the research not only significant but also represented a fairly substantial effect